Cultural Factor in Institutional Economics (Economic and Political Thought, 2012)
The article aims to highlight the humanization of the contemporaryeconomy and, what is connected with that, the necessity to take under broaderconsideration the factor of culture in the analysis of economic phenomena.The discussion has a theoretical character and results from research beingcarried out for several years by Warsaw School of Economics in cooperationwith the scholars of Lazarski University in Warsaw. The research concernedcultural conditions of location and interdisciplinary formation of principlesof balanced economic development. The basis for the theses formulatedin the article is a methodological consideration of a broadened concept of“institutional economics”, which makes it possible to take into considerationthe so-called “soft” factors and development conditions in the interpretationalanalysis. As culture is a manner of speaking about collective identities, it isbecoming an inseparable element of exercising choice between economicculture and barbarism. The collective conscience of the entities of socialand economic life should move faster towards contemporary institutions’operating in the modern civilization style. Adoption of Prof. A. Kłosowska’sstatement that culture is also the behavior of people involved in economicprocesses together with the products and results of such behavior can helpeconomists in the promotion of these processes. The general conclusion isthat it is necessary to analyze economic phenomena in a broader, humanisticand scientifically interdisciplinary manner.